ASSESSMENT OF GROUNDWATER QUALITY USING PHYSIOCHEMICAL AND GEOCHEMICAL ANALYSIS IN THE VICINITY OF LEI NALA, ISLAMABAD, PAKISTAN - Munir, S.; Mashiatullah, A.; Mahmood, S.; Zafar, M.; Javed, T.; Khan, M. S. (The Nucleus, 2011)
Quality of groundwater samples in vicinity of Lei Nala in Islamabad was assessed using physio-chemical and geochemical parameters. Lei Nala was sampled at four different locations, ten shallow groundwater samples (upto 200 feet) and twelve deep groundwater samples (>200 feet) were collected for analysis. Absence of carbonate ions (CO3 -2) in all groundwater samples indicates presence of limestone dissolution giving rise to bicarbonate and ultimately Ca-Mg type waters. Piper diagram reveals dominance with 53.86 % of Ca-Mg-type of water in the studied area. For anion concentration, HCO3-type of water predominated with 96.15 % samples. There is no significant change in the hydrochemical facies in the study area, indicating that most of the major ions are natural in origin which is due to the fact that groundwater is passing through sedimentary rocks and dissolves Margalla Hill Limestone thus dominating HCO3 and Ca-Mg facies.